The Mechanistic Target of Rapamycin Mediates Clostridium perfringens-Induced Chicken Necrotic Enteritis Attenuated by Secondary Bile Acid Deoxycholic Acid - Mohit Bansal; Tahrir Alenezi; Ying Fu; Janashrit Shrestha; Ayidh Almansour; Hong Wang; Anamika Gupta; Rohana Liyanage; Xiaolun Sun (Microorganisms)
Clostridium perfringens is a prevalent gut bacterial pathogen in humans and animals. This study investigated the role of the mechanistic targets of rapamycin (mTOR) and deoxycholic acid (DCA) on C. perfringens intestinal infection. Chickens were sequentially infected with Eimeria maxima and received the mTOR inhibitor rapamycin and DCA. C. perfringens-induced necrotic enteritis (NE) was evaluated using body weight gain (BWG), histopathology, bile acids, pathogen colonization, cell infiltration and death, and gene expression. The significant difference of p < 0.05 was analyzed by one-way ANOVA and multiple comparisons. Notably, rapamycin strongly reduced the subclinical and clinical NE histopathologies. DCA and DCA combined with rapamycin alleviated clinical NE and BWG loss. Rapamycin, DCA, and DCA + rapamycin attenuated bile acid reduction in NE birds, and they also reduced immune cell infiltration into the intestinal lamina propria as well as immune cell migration in vitro. At molecular levels, DCA and DCA + rapamycin reduced proinflammatory IFNγ, MMP9, IL23, and IL17 gene expression. Rapamycin, DCA, and DCA + rapamycin reduced NE-induced intestinal cell apoptosis. Together, these results suggest that mTOR signaling mediates C. perfringens-induced ileitis, and combining mTOR inhibition and DCA improves the intervention efficacy against NE ileitis and BWG loss.